Comparison of Hydrocolloid Dressings (Duoderm) with Povidone -Iodine Dressings in Diabetic Foot Ulcer. - Gul-e-Lala , Shaista Akhter , Faryal Azhar , Tousief Fatima , Naheed Akhtar , Faisal Bhopal (Journal of Rawalpindi Medical College, 2014)
Background : To compare effects of hydrocolloid dressings with povidone-iodine dressings in debrided diabetic foot regarding fast wound healing and reducing amputation. Methods: In this descriptive study patients with diabetic foot were enrolled. In-group A dressings was done with hydrocolloid while in-group B dressing was done with povidone –iodine. Wounds were assessed for depth ischemia classification. Vasculopathy, neuropathy and osteomyelitis were assessed. Parenteral antibiotics based on culture sensitivity were given. Insulin was used according to sliding scale. Split Thickness skin grafting was performed for all wounds > 5 cm if the wounds were found to be clean .Wounds < 5 cm in diameter were allowed to epithelize and heal without Split thickness skin graft. The total healing period was measured by the number of days from the date of initial debridement to the date of the Split thickness skin grafting or complete epithelization. Results: Mean number of days of healing by complete epithelization for group A (n= 70/140) were 40.87 ± 14 . days and mean number of days of healing by complete epithelization for group B patients were 47.16 ± 17.52 days (p- value < 0.05; significant). Conclusion: Hydrocolloid (duoderm) is a more effective and safe treatment in promoting wound healing in diabetic foot ulcers